Business Plans for Filmmakers - Cones, John W. (Book collections on Project MUSE., 2010)
The practical and legal aspects of writing a business plan for a film venture can be daunting to navigate without a firm grasp of know-how. With this in mind, John W. Cones's Business Plans for Filmmakers arms independent movie-makers and students with everything they need to successfully tackle the confusing intersection of law, business, and art when creating a business plan for a movie. This pragmatic volume offers plenty of examples and strategies for success, sharing straightforward insight into some of the toughest challenges independent filmmakers face when enco.